Increasing production capacity with drying oven and administrative order in the cassava cracker industry (Sari Potato) in Mulyoagung-Dau-Malang Village - sugeng hadi susilo; Muhammad Arif Nur Huda; Maskur Maskur; Nurhadi Nurhadi; Imam Saukani; Sanita Dhakirah (Journal of Community Engagement, 2025)
The COVID-19 pandemic has had a significant impact on Indonesia's economy, with reduced purchasing power and job losses, highlighting the need for the strategic role of Micro, Small, and Medium Enterprises (MSMEs) in economic recovery. In Mulyoagung Village, East Java, cassava cracker MSMEs face challenges in increasing production capacity due to traditional drying methods that depend on sunlight, which is unreliable during the rainy season. This study proposes the adoption of a drying oven technology as a solution to enhance production efficiency and capacity. By implementing this technology, the production of cassava crackers increased from 200 kg/day to 500 kg/day, a 2.5-fold improvement. Additionally, the study addresses the administrative issues within MSMEs, specifically the lack of structured financial record-keeping. Through training in financial management and the use of break-even point (BEP) analysis, MSMEs were able to improve their financial tracking and decision-making processes. The combination of technological improvement and better administrative practices not only boosted production but also improved the competitiveness of the MSMEs in local and regional markets. This project demonstrates the importance of applying appropriate technology and effective management to overcome operational challenges and foster long-term business sustainability.